NOSTALGIA, JATI DIRI, DAN SIMBOL SAKRAL EMPAT PUISI PADI DALAM PERSPEKTIF EKOKRITIK - Dewi, Novita (Balai Bahasa Provinsi Daerah Istimewa Yogyakarta, 2023)
This qualitative-interpretative research aims to uncover the imagination and meaning of rice in four poems from Southeast and East Asian countries: Vietnam, Singapore, Indonesia, and Korea. Rice is an essential part of Asian culture. It has become a significant and spiritual symbol for the people in this region, serving as more than simply a basic meal. The study seeks to investigate whether the cultural and spiritual values of rice have resonance and dynamics with the current world concerns, such as the deterioration of social life and the devastation of the natural environment. The data in the form of words from the following poems, i.e., “The Poem I Can’t Yet Name” by Nguyễn Phan Quế Mai, Eileen Chong’s “Burning Rice”, “Padi yang Tak Berputik” by Ni Wayan Kristina, and “Spoonful of Rice” by Hi-Dong Chai are procured from both printed and internet sources. The analysis is carried out using techniques that are commonly employed in poetry analysis, i.e., reading, inferring, and interpreting. Insights from ecocritical perspectives are also taken into account in the analysis. The results showed that (1) Locality colored each poem in accordance with the different backgrounds of the poets; (2) Rice emerges as nostalgia, identity, and a symbol of sacred culture. Even if it may be diminished with time, modernity, and environmental damage, the varied imaginations and meaning-making of rice are still treasured here.Penelitian kualitatif-interpretatif ini bertujuan menguak imajinasi dan makna padi dalam puisi dari empat negara di Asia Tenggara dan Asia Timur, yakni Vietnam, Singapura, Indonesia, dan Korea. Padi menjadi bagian penting dalam kehidupan bangsa Asia. Lebih dari sekadar sumber makanan pokok, padi menjadi simbol yang hakiki dan suci bagi masyarakat di kawasan ini. Kajian ini hendak melihat apakah nilai-nilai kultural dan spiritual padi relevan dan berdinamika dengan tantangan global saat ini, antara lain rusaknya lingkungan alam dan merosotnya kehidupan sosial. Data penelitian yang dipakai adalah larik-larik puisi berikut yang diambil dari sumber cetak dan internet: “The Poem I Can’t Yet Name” [Puisi Tanpa Nama] karya Nguyễn Phan Quế Mai, “Burning Rice” [Nasi Gosong] oleh Eileen Chong, “Padi yang Tak Berputik” karya Ni Wayan Kristina, dan “Spoonful of Rice” [Sesendok Nasi] karya Hi-Dong Chai. Analisis data dilakukan melalui metode yang lazim dipakai dalam mengkaji puisi, yakni pembacaan, penafsiran, dan pemaknaan. Perspektif teori ekokritik juga dipakai dalam analisis. Hasil penelitian menunjukkan bahwa (1) Lokalitas mewarnai setiap puisi sesuai dengan latar belakang masing-masing penyair; (2) Padi direpresentasikan dan dimaknai sebagai nostalgia, identitas, dan penanda kultural yang sakral. Beragam imaginasi dan pemaknaan tentang padi ini tetap dirawat meskipun mungkin melesap bersama waktu, modernitas, dan kerusakan lingkungan.